An international cross-sectional investigation on social media, fitspiration content exposure, and related risks during the COVID-19 self-isolation period - Cataldo, Ilaria (2022)
With the global COVID-19 pandemic, governments from many countries in the world implemented various restrictions to prevent the SARS-Cov-2 virus's spread, including social distancing measures, quarantine, in-home lockdown, and the closure of services and public spaces. This led to an in-creased use of social media platforms to make people feel more connected, but also to maintain physical activity while self-isolating. Concerns about physical appearance and the desire to keep or reach a muscular and toned ideal body, might have further reinforced the engagement in fitness-related social media activities, like sharing progresses in training achievements or following more fitness contents on popular profiles. To better understand the underlying relation among these factors, the present study investigates 729 responses to the Exercise Addiction Inventory (EAI), the Appearance Anxiety Inventory (AAI), the Self-Compassion Scale (SCS) and their association to social media usage and compares the results cross-culturally in five countries (Spain, Lithuania, United Kingdom, Japan, and Hungary). Findings highlight significant differences between males and females, espe-cially in regard to the time spent online (U = 477.5, p = 0.036). Greater levels of appearance anxiety were associated with the exposure to fitness-related contents on social media. These results strongly confirm the previously highlighted association between fitspiration media and body image anxiety predominantly in females. Clinical implications and future considerations in terms of prevention and treatment in a situation of global emergency are also discussed.